2022
DOI: 10.3390/jcm11123422
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Atopic Dermatitis and Cutaneous Infectious Disorders Using Sequential Pattern Mining: A Nationwide Population-Based Cohort Study

Abstract: According to previous studies, the increased risk of cutaneous infectious disorders in patients with atopic dermatitis (AD) is related to impaired epidermal function, abnormal systemic immune function, and lower antimicrobial peptides. In this study, we analyzed the association between AD and cutaneous infectious disorders in the real world using sequential pattern mining (SPM). We analyzed National Health Insurance data from 2010–2013 using SPM to identify comorbid cutaneous infectious diseases and the onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(34 reference statements)
0
2
0
1
Order By: Relevance
“…**Punto de buena práctica: la DA se asocia con un riesgo mayor de trastornos infecciosos cutáneos. Un estudio reciente de cohorte encontró relevancia alta por frecuencia elevada de comorbilidades infecciosas para impétigo, molusco contagioso y otitis media, su identificación puede ayudar a prevenir el empeoramiento de la DA mediante la prevención y el manejo adecuados de la afección 156 . Las exacerbaciones agudas de los síntomas oculares y el deterioro visual justifican la referencia urgente a oftalmología 157 .…”
Section: S2(95)unclassified
“…**Punto de buena práctica: la DA se asocia con un riesgo mayor de trastornos infecciosos cutáneos. Un estudio reciente de cohorte encontró relevancia alta por frecuencia elevada de comorbilidades infecciosas para impétigo, molusco contagioso y otitis media, su identificación puede ayudar a prevenir el empeoramiento de la DA mediante la prevención y el manejo adecuados de la afección 156 . Las exacerbaciones agudas de los síntomas oculares y el deterioro visual justifican la referencia urgente a oftalmología 157 .…”
Section: S2(95)unclassified
“…Beyond retail, SPM was applied as a methodology to investigate relationships among medical events, and develop predictive models for extensive healthcare data in human medicine [1,8]. SPM-derived studies applied to medicine have demonstrated promising outcomes, including disease susceptibility prediction [9,10], improved understanding of disease progression patterns [11,12], identification of revisit patterns [13,14], enhanced pharmacovigilance for medication safety [15,16], and the exploration of relationships between medical conditions [17,18]. Despite several limitations, including variations in data quality, privacy concerns, the complexity of developing predictive models, and ethical considerations regarding data usage and transparency, medical research employing SPM has been actively reported to date [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of cutaneous warts in primary school children is high (up to 33%) 2 . Children suffering from AD have an increased risk for cutaneous warts (age/sex‐adjusted odds ratio [aOR] = 1.10, 95% confidence interval [CI]: 1.05–1.17), and an even higher risk for developing molluscum contagiosum (aOR = 5.27, CI: 5.13–5.42) 3 . Although most warts eventually resolve spontaneously, 2 many are recalcitrant owing to intricate immune escape mechanisms inherent both to human papillomavirus 4 as well as molluscum contagiosum virus 5 .…”
mentioning
confidence: 99%